2013
DOI: 10.1111/1462-2920.12305
|View full text |Cite
|
Sign up to set email alerts
|

Two‐role model of an interaction network of free‐living γ‐proteobacteria from an oligotrophic environment

Abstract: Antagonistic interactions are frequently observed among bacteria in the environment and result in complex networks, which could promote co-existence, and therefore promote biodiversity. We analysed interactions of aquatic bacteria isolated by their ability to grow in Pseudomonas isolation agar from Churince, Cuatro Ciénegas, Mexico. In the resulting network, highly antagonistic and highly sensitive strains could be distinguished, forming a largely hierarchical structure. Most of the highly antagonistic strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
(111 reference statements)
5
28
0
Order By: Relevance
“…Due to the lack of comprehensive experimental data on interactions, quantitative studies of microbial ecosystems have so far relied on theoretical modeling (15,20,21) or sequencing methods (22) or have focused on incomplete subcommunities (23). Indeed, only a few studies have experimentally quantified ecological interactions in different microbial ecosystems on a larger scale (23)(24)(25)(26). Importantly, these interactions can potentially alter the efficacy of drug treatments as bacteria can protect others from the effect of antibiotics (27), in the simplest case by just degrading the drug (13,28,29).…”
mentioning
confidence: 99%
“…Due to the lack of comprehensive experimental data on interactions, quantitative studies of microbial ecosystems have so far relied on theoretical modeling (15,20,21) or sequencing methods (22) or have focused on incomplete subcommunities (23). Indeed, only a few studies have experimentally quantified ecological interactions in different microbial ecosystems on a larger scale (23)(24)(25)(26). Importantly, these interactions can potentially alter the efficacy of drug treatments as bacteria can protect others from the effect of antibiotics (27), in the simplest case by just degrading the drug (13,28,29).…”
mentioning
confidence: 99%
“…D0b inhibited 18 of the 20 targets (Table 1). Similarly, Aguirre-von-Wobeser et al (27), using the spot-lawn method, also found Pseudomonas spp., isolated from an aquatic environment, were the most highly antagonistic strains. Published reports show plant and clinical strains of Pseudomonas (e.g., Pseudomonas putida, P. fluorescens, and other Pseudomonas spp.)…”
Section: Discussionmentioning
confidence: 84%
“…A review of the literature shows that the promotion of bacterial growth by effector isolates has been less frequently reported compared to inhibition. Possible reasons include the spot-lawn method, a test format not readily detecting growth promotion, being a primary method used in many previous studies (8,26,27) and that primary interests of applied food microbiology are in extending shelf-life and food quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations